Recovery of a Recombinant Salmonid Alphavirus Fully Attenuated and Protective for Rainbow Trout - Moriette, Coralie (American Society for Microbiology, 2006)
Sleeping disease virus (SDV) is a member of the new Salmonid alphavirus genus within the Togaviridae family. The single-stranded RNA genome of SDV is 11,894 nucleotides long, excluding the 3′ poly(A) tail. A full-length cDNA has been generated; the cDNA was fused to a hammerhead ribozyme sequence at the 5′ end and inserted into a transcription plasmid (pcDNA3) backbone, yielding pSDV. By transfection of pSDV into fish cells, recombinant SDV (rSDV) was successfully recovered. Demonstration of the recovery of rSDV was provided by immunofluorescence assay on rSDV-infected cells and by the presence of a genetic tag, a BlpI restriction enzyme site, introduced into the rSDV RNA genome. SDV infectious cDNA was used for two kinds of experiments (i) to evaluate the impact of various targeted mutations in nsP2 on viral replication and (ii) to study the virulence of rSDV in trout. For the latter aspect, when juvenile trout were infected by immersion in a water bath with the wild-type virus-like rSDV, no deaths or signs of disease appeared in fish, although they were readily infected. In contrast, cumulative mortality reached 80% in fish infected with the wild-type SDV (wtSDV). When rSDV-infected fish were challenged with wtSDV 3 and 5 months postinfection, a long-lasting protection was demonstrated. Interestingly, a variant rSDV (rSDV(14)) adapted to grow at a higher temperature, 14°C instead of 10°C, was shown to become pathogenic for trout. Comparison of the nucleotide sequences of wtSDV, rSDV, and rSDV(14) genomes evidenced several amino acid changes, and some changes may be linked to the pathogenicity of SDV in trout.